2012
DOI: 10.1002/pbc.23413
|View full text |Cite
|
Sign up to set email alerts
|

A new tool for the assessment of satisfaction with iron chelation therapy (ICT‐Sat) for patients with β‐thalassemia major

Abstract: A new clinically based ICT-Sat tool was developed and revealed good psychometric characteristics. Adherence to ICT was better correlated with "perceived effectiveness" and SF level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…found that adherence and satisfaction to DFO is generally poor and a patient's attitude to adherence can change over time . The availability of oral iron chelators may contribute to improved compliance, especially among pediatric and adolescent patients . The combined DFP/DFX in our study had the best patients' compliance and satisfaction.…”
Section: Discussionmentioning
confidence: 68%
“…found that adherence and satisfaction to DFO is generally poor and a patient's attitude to adherence can change over time . The availability of oral iron chelators may contribute to improved compliance, especially among pediatric and adolescent patients . The combined DFP/DFX in our study had the best patients' compliance and satisfaction.…”
Section: Discussionmentioning
confidence: 68%
“…For our patients, iron chelation therapy, particularly oral chelation, significantly and negatively impacted HRQoL. Leafy MS et al 35 observed all patients experienced burden with chelation, no matter which type. Similarly, Thavorncharoensap et al 10 stated that iron chelation treatment was associated with poorer HRQOL.…”
Section: Discussionmentioning
confidence: 55%
“…However, DFX has restrictive administration instructions (eg, take on an empty stomach at least 30 min before food; disperse tablets by stirring in water or juice) [19] and known associations with suboptimal palatability, tolerability, and gastrointestinal (GI) side effects [19, 20], which may negatively impact compliance [20]. This direct relationship between treatment satisfaction and compliance among ICT and chronically-treated patients has been demonstrated previously [2123], as has the relationship between perceived burden of ICT and poor compliance [22]. …”
Section: Introductionmentioning
confidence: 84%